PSYCHOLOGICAL CHARACTERISTICS OF PROFESSIONAL COMMUNICATION AND SPEECH CULTURE IN LEGAL PRACTICE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article analyzes the psychological features of professional communication and speech culture in a lawyer's professional activity, specifically the role of a lawyer's effective communication skills in their interaction with clients, judicial authorities, and law enforcement agencies. The significance of speech as a means of transmitting information and managing emotions in professional activity is highlighted. The article explores issues of establishing a reliable psychological connection between a lawyer and the subject (client/suspect), speech expressiveness, emotional stability, and preventing professional deformation from the perspective of legal psychology. The features of enhancing professional authority through adherence to legal norms, sincerity, empathy, and speech culture are also highlighted. In conclusion, it is substantiated that the correct use and clarity of legal terms in a lawyer's speech is the foundation of practical effectiveness.